Gauging Spontaneous Language Gain : Spontaneous Written Language Gain in an Upper-Level College German Course - Luginbill, Annisa; Lindseth, Martina (My University, 2018)
Reaching the Advanced level of language proficiency according to the national standards of the American Association of Teachers of Foreign Languages (ACTFL) is a high stakes target at many universities across the United States, as well as a benchmark for graduation at UWEC. Much research has been done regarding the development of advanced level language functions. Most upper level classes focus on developing reflective writing, writing which grants unlimited time to the student and use of manipulatives, such as dictionaries. However, in a real world setting, students also need advanced level proficiency in spontaneous writing within a certain time limit and without access to said manipulatives to write cohesive and comprehensible emails, memos, and reports in a timely fashion.
Color poster with text, charts, and graphs.
Keywords: Spontaneous writing; Writing evaluation; Posters